Analisis Kuat Lentur Nominal Balok Komposit Menggunakan Program Berbasis Android - Saputro, Rifki Ananda; Suyadi, Suyadi; Zakaria, Ahmad (Universitas Lampung, 2015)
Composite beam is a combination of concrete and steel profiles. Nominal flexural strengthanalysis of composite cross-section can be calculated manually, but it takes a long time or are notefficient when calculating the nominal flexural strength analysis of composite beams. In this study,it can be a formulation of the problem is how to apply the analysis to the nominal flexural strengthcomposite into android-based programs. The purpose of this study in this thesis is to simplify thecalculation of the nominal flexural strength analysis of composite beams using android basedapplication program. Object-based research to create a program that profiles IWF android withconcrete (composite beam).In the implementation of this study using two methods: the method of literature study (study oftheory) and methods of software development (analysis, design, coding, and testing).This program has been tested with manual calculations that show the results accordingly. Fromthe test results indicate that the ease of use of program-based program that android is moresimple and easy to use in the field.Keywords: composite beam, android, nominal flexural strength analysis